STABILITY OF PHYLLANTHUS EMBLICA EXTRACT IN LIPOSOMES - Kongiampitee, P.; Nimmannit, U. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Phyllanthus emblica L. (P. emblica) has many benefits in its biological effects, including anti-oxidant activity, anti-tyrosinase activity, anti-microbial activity and protection against radiation-induced chromosome damage. However, the stability is a major concern of the P. emblica extract. Therefore, the objective of this research is to compare the stability of the P. emblica extract in liposomes and buffer solutions at pH 5.5 and 7.4. The lipid compositions of liposomal membranes were egg phophatidylcholine (Lipoid E80) and cholesterol at 2:1 molar ratio with cholesterol ester as a stabilizer. The concentrations of P. emblica extract were varied at 1, 2, 3, 4 and 5 mg/mL. The encapsulation efficiency and chemical stability were determined by measuring the amount of total phenolic compounds using UV-VIS spectrophotometer. The highest percent encapsulation efficiency was found at 52.83% obtained from liposome formulation containing 1 mg/mL of P. emblica extract prepared at pH 5.5. In addition, the above preparation was stable at least 12 weeks when stored in a refrigerator at 4°C. The particle size of the liposomes stored for 0 and 12 weeks was not significantly different with the mean particle sizes of 5.790 + 0.756 and 5.553 + 0.647 µm respectively. Summarily, P. emblica extract in liposomes is more stable than that in buffer solutions.